THERMAL-MECHANICAL EFFECTS OF LOW-TEMPERATURE PLASTICITY (THE PEIERLS MECHANISM) ON THE DEFORMATION OF A VISCOELASTIC SHEAR ZONE - Kameyama M.; Yuen D.A.; Karato S.I. (My University, 1999)
We studied for the first time the effects of low-temperature plasticity on the formation of shear zones. A thermal-mechanical model has been developed for describing the shear deformation of Maxwell viscoelastic material with a rheology close to dry olivine. We employed a one-dimensional model with a half-width of L deforming under a constant velocity U at the boundary, and the spatially-averaged strain rate U/L was set to O(10-14) s-1. In addition to diffusion and power-law creep, we included deformation by low-temperature plasticity, called the Peierls mechanism, which is significant at low temperatures and has a strong exponential dependence on the stress. When a sufficient magnitude of heat is generated by the rapid conversion from elastically-stored energy into viscous dissipation, thermal instability takes place and the deformation localizes in a narrow region. By comparing the condition for thermal instability, we found that the low-temperature plasticity inhibits the development of thermal instability in shear zones in case of constant strain rate. The Peierls mechanism enhances deformation at a significantly lower stress compared to the rheology with solely diffusion creep and power-law creep. The enhanced deformation by low-temperature plasticity produces lower amount of dissipative heating, and thus stabilizes the shear zone. Comparing the stability between constant strain-rate and constant stress boundary conditions, we found that the Peierls mechanism exerts an opposite destabilizing effect in the case of constant stress. For dry olivine rheology and realistic magnitude of the strain rate, the effect of low-temperature plasticity is significant for temperatures between around 800 K and 1000 K. This finding suggests that the low-temperature plasticity may be crucial in determining the thermal-mechanical stability in the shallow portion of slabs.
Keywords: PLASTICITY; RHEOLOGY; THERMOMECHANICAL PROPERTIES; SHEAR ZONES; SUBDUCTION